An Investigation into the Corporate Governance of Limited Liability Partnerships in the Professional Services Industry - Cooper, Simon (2006)
The researcher would like to acknowledge the help and support that was given by family and friends. There is also recognition that without the co-operation of respondents, who were willing to give up their time and offer their advice, the thesis, would not have been possible. Finally, for their assistance throughout the whole of the dissertation I would like to thank Alistair Bruce, Edward Wray-Bliss and most importantly Tim Bailey.